B41 HD on chip : reconstituting the cortico-striatal network on microfluidics to study intracellular trafficking and synaptic transmission. (13th September 2016) - Virlogeux, Amandine; Cazorla, Maxime; Bruyère, Julie; Christaller, Wilhelm; Genoux, Aurélie; Charlot, Benoit; Saudou, Frédéric
Abstract : Most of the cellular or molecular studies in HD used so far separated cultures of striatal or cortical neurons. However, in the brain these neurons are connected and form a particular network that is defective in HD. The polarised nature of neurons and the size and density of synapses complicates the manipulation and visualisation of specific events taking place in axons or dendrites and of specific synaptic transmission within the cortico-striatal network. To overcome these limitations, we developed several microfluidic systems compatible with high-resolution videomicroscopy and connected to microelectrode arrays (MEA) to reconstitute and identify each component of the corticostriatal network. The microfluidic system directs the formation of identified synapses separately between cortical axons and striatal dendrites and soma. In parallel, a multielectrode substrate monitors and controls presynaptic and postsynaptic activity independently. Using this multicomplex system we are investigating how the trafficking of synaptic vesicles or mitochondria along axons is regulated by presynaptic and postsynaptic patterns in the corticostriatal network in health and HD. In addition, the system allows modifying the genetic status of the cortical or striatal neurons as a way to selectively investigate how disease neurons differentially affect pre or post-synaptic events in HD and overall alter synapse function.